Prognostic and Risk Stratification Value of Lesion MACC1 Expression in Colorectal Cancer Patients - Lin, Aifen; Zhang, Xia; Zhang, Rui- Li; He, Xiao-Fang; Zhang, Jian-Gang; Yan, Wei-Hua (Frontiers in Oncology, 2019)
The up-regulated metastasis-associated in colon cancer 1 (MACC1) expression and its clinical significance has been explored in a varity of malignancies. In this study, lesion MACC1 expression in 503 CRC patients (Ncolon=332, Nrectal=171) were analyzed with immunohistochemistry, and its correlation with clinical parameters, patient survival, and its impact on prognostic stratification were evaluated. Data revealed the survival of patient with MACC1high is markedly worse than that of MACC1low (mean overall survival: 80.1 months vs. 90.4 months; p=0.001) and is an independent prognostic predictor (hazard ratio=1.533; p=0.005). More importantly, for the first time, we demonstrated that MACC1 status exhibited a significantly prognostic power for stratified clinical parameters such as patient age and gender, particular TNM status and distinct AJCC disease stage. In summary, our findings indicated that MACK is a valuable prognostic and risk stratification biomarker for colorectal cancer patients.